Prehospital advanced airway management practices by advanced life support providers: A retrospective observational study of emergency medical service providers in South Africa - Burke, Jan (Division of Emergency Medicine, 2021)
Introduction: The skill of endotracheal intubation to achieve a definitive airway for critically ill and injured patients in the prehospital setting is frequently performed by advanced life support providers. Several methods may be utilised, including intubation without the use of medication, the use of sedatives or a rapid sequence intubation. There is a paucity of data available that assesses prehospital advanced airway intubation practices in South Africa. The aim of this study is to describe the advanced airway management practices of advanced life support providers across South Africa. Methods: A retrospective, observational study method was used (chart review). Electronic patient care records were sourced from private and public emergency medical services companies and collated accordingly. Results: A total of 704 cases were included. Intubation during cardiac arrest was the most common approach to airway management (n=280, 40%) followed by rapid sequence intubation (n=202, 28%), medication-facilitated intubations (n=152, 22%) and a nomedication approach (n=70, 10%). Successful intubation using an endotracheal tube was reported in 197 (98%) of rapid sequence intubation cases, 134 (88%) of the medication facilitated cases, 61 (87%) of no-medication cases and 228 (81%) of cardiac arrest cases. A first-pass success rate was described in 260 (79%) cases, with the cardiac arrest group having a first-pass success of 85%, followed by the rapid sequence intubation group (83%), the nomedication group (71%) and the medication facilitated group (61%). Hypotension and cardiac arrest were the most common adverse events. A total of 496 (70%) patients were alive at hospital handover. The average scene time and transportation time was 42 minutes and 24 minutes respectively for the rapid sequence intubation group, 42min and 27min for the medication facilitated group, 44min and 25min for the no-medication group and 57min and 16min for the cardiac arrest group. Discussion: The study described the prehospital airway management practices by advanced life support providers in South Africa. Rapid sequence intubation had the highest endotracheal intubation success rate overall and the lowest prevalence of adverse events. There was no statistical difference in survival between the rapid sequence intubation, medication facilitated and no-medication group. Due to a lack in standardised treatment guidelines, differences in fluid administration, post-intubation care, confirmation of placement and ventilation were noted. No standard approach to record keeping was found, with the quality of patient care records being variable. A standardised advanced airway management report would be beneficial as it would improve the quality of data recorded and allow for better comparisons to be made.